Digestibilidad del pasto Imperial Axonopus scoparius y Gamalote Paspalum fasciculatum - Bateman, John V.; Garza T., Rolando (Instituto Interamericano de Ciencias Agrícolas (IICA), 2025)
The digestibilities of Imperial Grass (Axonopus scoparius) and Gamalote (Paspalum fasciculatum) cut at eight weeks of age are reported. Imperial grass with 15.25% dry matter contained 55.43% TDN and 2181 Kcal of digestible energy per kilogram of dry matter. Gamalote with 21.20% dry matter contained 44.06% TDN and 1671 Kcal of digestible energy per kilogram of dry matter.